The Roots of Appearance and Persistence of Income Inequality: A case study of India - Mohammadi, Mohammad Hossein; Ghoreishi, Fardin (Journal of History Culture and Art Research, 2021)
Income inequality among various forms of inequality, these days has attracted the serious attention of policymakers, rulers and thinkers. Each of these three groups has tried to identify the causes of occurrence and continuity through their views and, of course, provide solutions to mitigate it. The beginning of the third millennium was accompanied by an intensification of income inequalities within countries, so that the efforts of the international community, which had previously been able to reduce poverty and absolute hunger in the framework of documents such as the Millennium Development Goals, to reduce it, so far has failed to alleviate it. Identifying the causes of the emergence and perpetuation of income inequality in different economies is very significant at a time when the threats posed by income inequality are estimated in important documents such as the Global Threat Report as significant as terrorism. The subject of this article is to examine the textual, institutional and global causes of the continuing income inequality in India, which has recorded a remarkable economic growth rate these days. In India, a set of factors including the roots of social system deficiencies, economic growth, globalization and its tools such as privatization and trade liberalization are among the main causes of continuing inequality in Indian society today, which seems to be a continuous process due to the priority of economic growth against the reduction of income inequality for different governments in this country.